Firm Size and Profitability: A Study of Listed Manufacturing Firms in Sri Lanka - Niresh, J.A.; Velnampy, T. (My University, 2014)
The purpose of this study is to explore the effects of firm size on profitability of quoted manufacturing firms in Sri Lanka. In this study, data of 15 companies which were active in Colombo Stock Exchange (CSE) between the years 2008 to 2012 has been used. As indicators of firm profitability, Return on Assets and Net Profit have been used whereas Total Assets and Total Sales have been utilized as indicators of firm size. Correlation and regression methods have been used in the empirical analysis. There is no indicative relationship between firm size and profitability of listed manufacturing firms, the findings reveal. In addition, the results showed that firm size has no profound impact on profitability of the listed manufacturing firms in Sri Lanka.
Keywords: firm size; Profitability